2015
DOI: 10.1167/iovs.15-17107
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Inherited Eye Defects by Systemic Hematopoietic Stem Cell Transplantation

Abstract: PURPOSE. Cystinosis is caused by a deficiency in the lysosomal cystine transporter, cystinosin (CTNS gene), resulting in cystine crystal accumulation in tissues. In eyes, crystals accumulate in the cornea causing photophobia and eventually blindness. Hematopoietic stem progenitor cells (HSPCs) rescue the kidney in a mouse model of cystinosis. We investigated the potential for HSPC transplantation to treat corneal defects in cystinosis. METHODS. We isolated HSPCs from transgenic DsRed mice and systemically tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 45 publications
3
29
1
Order By: Relevance
“…7). Similar protection has been demonstrated in the eyes and thyroid of Ctns -knockout mice, leading to near complete clearance of corneal cystine crystals and preservation of corneal structure 188 , as well as normalization of thyroid-stimulating hormone level and preservation of thyroid follicles, repectively 189 .…”
Section: Treatment and Therapeutic Perspectivessupporting
confidence: 66%
“…7). Similar protection has been demonstrated in the eyes and thyroid of Ctns -knockout mice, leading to near complete clearance of corneal cystine crystals and preservation of corneal structure 188 , as well as normalization of thyroid-stimulating hormone level and preservation of thyroid follicles, repectively 189 .…”
Section: Treatment and Therapeutic Perspectivessupporting
confidence: 66%
“…Together, these data demonstrated that wild-type mouse HSPC transplantation in 2-month-old YG8R mice rescued the progressive neurobehavioral and muscular deficits characteristic of this FRDA animal model. In contrast to our previous findings in a cystinosis model (14, 16), the YG8R mouse exhibiting the lowest percentage of donor-derived cell engraftment (35%; table S1) still exhibited physiological rescue of the behavioral deficits (table S2). …”
Section: Resultscontrasting
confidence: 99%
“…After euthanasia, retinas were isolated and processed immediately following the method described by Rocca et al 27 In brief, the retinas were homogenized using a precellys 24-tissue homogenizer (Bertin Technology, Siège, France). Their total RNA was prepared using the RNeasy Lipid Tissue Mini Kit (Qiagen, Germantown, MD, USA) according to the manufacturer's instructions and was then quantified using a NanoDrop ND 1000 spectrophotometer (Thermo Fisher Scientific).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%